Implementation of electronic stethoscope for online remote monitoring with mobile application - Sugondo Hadiyoso; Dieny Rofiatul Mardiyah; Dadan Nur Ramadan; Asril Ibrahim (Bulletin of Electrical Engineering and Informatics, 2020)
The stethoscope is a piece of medical standard equipment that isused by a physician for an initial examination of the patient. Generally, the stethoscopeis used for auscultating sounds which are generated by the workings of organ systems such as cardiac, lung or digestive. In the present condition with the growing number of the patient population, it has an impact on the burden of hospitals and medical practitioners. So that treatment is not optimal, especially patients who need continuous monitoring. Thus it needs a system that can work dynamically, flexibly and remotely based. This paper focuses on the implementation of the electronic stethoscope which is integrated with a mobile phone as the modality of online data transmission through the internet network. The prototype of an electronic stethoscope uses condenser mic, pre-amplifier, wide bandpass filter (20 Hz-1 KHz) and audio amplifier. The maximum gain is 28.63 dB in the 20 Hz-690 Hz frequency range. The signal output can be connected to the android mobile through the jacked phone to be stored in MP3 format and then sent to the cloud server for further monitoring and analysis. The application called “Steder” supports realtime communication between patient and physician for medical check-up, consultation, and discussion activities.